PREDICTING THE CLEAVAGE SITES OF MULTIPLE PROTEASES FAMILIES ON RICE ALPHA AMYLASE ISOZYME 3D SEQUENCE - Ayu Oshin Yap Sinaga; David Septian Sumanto Marpaung (Universitas Panji Sakti, 2020)
Proteases is a proteolytic enzyme that often determined the crucial process in degradation pathway occurred in all of organisms. Prediction of novel protease is important action to design the protease inhibitor. In the secretion of rice αAmy3 protein in outside cells will be followed by secretion of recombinant protein target and proteolytic enzymes together, which means potentially also degraded the recombinant protein target In this study, the proteases was detected in rice αAMY 3D protein sequences. Our study resulted the 3 major proteases appeared in rice αAMY 3D protein sequences, they were cysteine proteases, serine proteases and metalloproteases. Based on the literature, such proteases also appeared in rice suspension cells. Design the inhibitor for such proteases will be suggested for reduction of proteases level. DOI: 10.37637/ab.v3i1.449